Countering Islamophobia in Europe - Law, Ian; Easat-Daas, Amina; Merali, Arzu; Sayyid, S. (Mapping Global Racisms, 2019)
1. Introduction; Ian Law, S. Sayyid, Arzu Merali & Amina Easat-Daas -- 2. Islamophobia as a Key Contextual Factor in Human Rights Adjudication; Ilias Tripolitis -- 3. Countering Islamophobia in the UK; Arzu Merali -- 4. Countering Islamophobia in Greece; Matilda Chatzipanagiotou & Iason Zarikos -- 5. Countering Islamophobia in Hungary; Zsuzsanna Vidra -- 6. Countering Islamophobia in the Czech Republic; Karel Čada &Veronika Frantová -- 7. Countering Islamophobia in Portugal; Marta Araújo, Silvia Rodríguez Maeseo & Max Ruben Ramos -- 8. Countering Islamophobia in France; Andrea Bila -- 9. Countering Islamophobia in Belgium; Elsa Mescoli -- 10. Countering Islamophobia in Germany; Luis Manuel Hernández Aguilar -- 11. A New Counter-Islamophobia Kit; Ian Law, S. Sayyid & Amina Easat-Daas